Monitoring historical masonry structures with operational modal analysis: two case studies - Ramos, Luis F. (2012)
The paper addresses two complex case studies of modal and structural identification of monuments in Portugal: the ClockTower of Mogadouro and the Church of Jerónimos Monastery, in Lisbon. These are being monitored by University of Minho with vibration, temperature and relative air humidity sensors. Operational modal analysis is being used to estimate the modal parameters, followed by statistical analysis to evaluate the environmental effects on the dynamic response .The aim is to explore damage assessment in masonry structures at a nearly stage by vibration signatures, as a part of a health monitoring process that helps in the preservation of historical constructions. The paper presents the necessary preliminary dynamic analysis steps before the monitoring task, which includes installation of the monitoring system, system identification and subsequent FE model updating analysis, automatic modal identification and investigation of the Influence of the environment on the identified modal parameters.